Enabling LTE and WiFi Coexisting in 5 GHz for Efficient Spectrum Utilization - Hongyu Sun; Zhiyi Fang; Qun Liu; Zheng Lu; Ting Zhu (Journal of Computer Networks and Communications)
Due to the increasing mobile traffic demands in cellular network, researchers have proposed the coexistence of LTE and WiFi technologies in 5 GHz unlicensed bands. Therefore, how to efficiently utilize the spectrum in 5 GHz becomes extremely important. To avoid the channel access conflicts, current LTE Unlicensed (LTE-U) technology introduces the duty cycle of LTE, while License-Assisted Access (LAA) technology introduces Listen-Before-Talk (LBT) mechanism. While these two technologies improve the spectrum utilization by using time division access schema, we believe that more efficient spectrum utilization can be achieved by enabling simultaneous transmissions from LTE and WiFi. In this paper, we propose a novel method (i.e., Low Amplitude Stream Injection (LASI) method) to enable the simultaneous transmissions of WiFi and LTE frames in the same channel and recover the data from the conflicts. To further utilize the LASI method, we introduce the Conflict-Tolerant Channel Allocation (CTCA) algorithm to optimize the channel allocation and achieve more efficient spectrum utilization in 5 GHz. Extensive simulation results show that our approach achieves lower latency and higher throughput. Compared with the state-of-the-art LTE-U and LAA technologies, our approach can improve the spectrum efficiency 2.9 times.